Let's learn economics - Azman, Hartini; Yahaya, Siti Norbaya; Sufian, Atirah (Penerbit UTeM Press, 2021)
Module is designed for first-year undergraduates taking economics courses. Students will be introduced to key economic concepts. Includes economic analysis covering microeconomics and macroeconomics. covers the basic economic nature and system, demand and supply and market structures.